Diversity and Collections of Orchids in the Forest Waifoi Raja Ampat and Sorong Nature Park- West Papua - Tirta, IG. (Proceeding International Conference on Global Resource Conservation, 2013)
Raja Ampat regency has 610 islands, located at 2025 N latitude and 4025 S latitude, 130o-132o 55 E longitude. The total area covers 6791 km2. Waigeo island in Waisai district of the Raja Ampat Regency is the priority research and conservation, because their properties in Raja Ampat development very fast. Mentioned above the base of the research were conducted in Waifoi forest (Waigeo) and Sorong Nature Park. The aims of this research are to inventory and collect the orchid at Waifoi forest and Sorong Nature Park. The research was done in 28 days from June 11 to July 9, 2007 with exploration method. Results show that 143 species of 52 Genus were found and collected. Most of the collections are Dendrobium genus (32 of species). Key words: collections, Diversity, orchid, Raja Ampat, Sorong, Waifoi forest